REVIEW OF STRENGTHENING TECHNIQUES AND MECHANICAL TESTING FOR UNREINFORCED MASONRY - Mustafaraj, Enea; Yardim, Yavuz (MATTER: International Journal of Science and Technology, 2017)
In this paper, it is presented a collection and a critical review on the most significant research done on unreinforced masonry, types of testing, behavior and strengthening techniques to improve structural its structural performance. Furthermore, these researches are categorized and critically analyzed to benefit verities of them and help further understand behavior of URM. This study provides summary and guidance for researchers who are working on strengthening, modeling and retrofitting methods